(untitled) (INNOVATIVE ECONOMY, 2020)
Chykalova A.S. LATEST TOOLS OF COMMUNICATION POLICY IN THE EXCHANGE ACTIVITIES OF BUSINESS STRUCTURES Purpose. The purpose of the stated research is justification of proposals for the use of effective marketing communication tools which are relevant at the current stage of the society development. Methodology of research. General scientific and special research methods were used in the process of conducting the research, in particular: the method of strategic analysis – in justifying the directions of communication policy in exchange activities; systematic approach – when analyzing the modern marketing concepts, the method of comparisons (when studying the current situation at the market of marketing services in the sphere of exchange activities of business structures); method of structural grouping (when determining alternative tools for communication policy). Findings. It is established that the state of the modern economy, its effective planning is closely related to the activation of business structures and exchange activities. It is determined that nowadays both exchange markets and business structures prefer either classical methods and forms of advertising campaign, or attracting marketing experts to perform temporary work on conditions of remote access. It is justified that the use of traditional tools of marketing communications to promote the product has become a thing of the past: the consumer has changed, as well as his attitude to traditional advertising; a new concept of “market literacy of the consumer” has appeared, when information is obtained from independent sources and Internet sites, paying great attention to feedbacks. Accordingly, manufacturers have to shift the emphasis to the emotional attractiveness of the product. A list of factors influencing the effectiveness of communication policy of business structures in the current economic conditions has been formed. Originality. Based on the analysis classical and latest tools of marketing communications, the directions of effective promotion of goods and services in existing and new domestic and foreign markets are substantiated. The directions of transformation of the marketing communications complex on the innovative basis, taking into account technologies that correspond to the realities of a certain time, are determined. Practical value. The results of this research can be used in the practical activities of business structures in the field of cooperation with exchange markets and introduction of the latest communication tools. The results could also be used as the basis for further research on the identification of alternative methods and tools for communication policies in exchange and business activities. Key words: communication policy; classical and latest tools; business structures; exchange activities; marketing communications.